ZakÄtÄbility from the Salary of Muslim Civil Servants in Nasarawa State, Nigeria - Salihu Liman Mairafi; Sulaiman Yahaya; Aliyu Muhammad Maishanu (Universitas Muhammadiyah Yogyakarta, 2022)
This research aims to create awareness among Muslim civil servants that they can pay zakÄt from their savings with the cooperative society. Muslim civil servants who joined cooperative societies in their various places of work, their salary every month and from the source used to be deducted and kept under the custody of the cooperative society. Some save a huge amount of money and leave it alone until retirement, but unfortunately, when the money reaches the prescribed scale (niá¹£Äb) for zakat, many are unaware of giving the right of AllÄh to the beneficiaries. The methodology used in this work was library-based and interviews with the relevant stakeholders. This work is significant in the sense that it would educate those who are not aware of paying zakÄt from their salary that accumulates under the care and trust of cooperative society, and also the researchers can use it as reference material. In conclusion, it encourages Muslim civil servants to always seek knowledge about their money and pay the zakÄt. The findings revealed that the management of the Islamic cooperative society used to inform members when their funds were due for zakÄt. No matter what, we recommend that zakÄt should be paid.